Photothermal Effect: The Amygdaloidal Nano-Structure Based on Bi2S3 for the Enhanced Degradation of Rhodamine B Under Irradiation by NIR - Yin, Xiuzhao; Zhang, Yunyu; Ai, Fujin (Frontiers in Chemistry, 2021)
A key auxiliary role of the photothermal effect in the enhancement degradation of pollutant under irradiation by near-infrared (NIR) have become a recent research focus. Herein, a novel amygdaloidal nanophotocatalyst, Bi2S3, was synthesised by a traditional approach using a hydrothermal process, in which Bi2S3 nanostructure were spread out like a peacock’s tail. The produced Bi2S3 photocatalyst exhibited excellent performance in the rapid degradation of Rhodamine B (RB) in industry. It has been proved that the photothermal effect is mainly responsible for the rapid degradation of RB under NIR laser irradiation. Moreover, it has been found that the photothermal effect could not degrade the products with NIR radiation in dark. However, with the support of visible radiation, the photothermal effect of the Bi2S3 photocatalyst has enhanced degradation of RB (degradation rate 90% under 1 h). So this novel structure exhibited a potential ability for degrading of pollution in industry or agriculture.NIRE